2010
DOI: 10.1016/j.proche.2009.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of coulometric array detection in analysis of beverages and plant extracts

Abstract: This paper summarises the findings obtained by using multi-electrode detector CoulArray in HPLC analysis of biologically active compounds. The methods for analysis of selected phenolic compounds were optimized. Optimal conditions of separation and detection were applied to real sample analysis. White and red wines as well as meads were analyzed and the content of phenolic acid was evaluated. Further the roots of Japanese knotweed were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…In comparison with other reports that employed HPLC-ECD [ 35 , 47 , 48 ] for phenolic acid detection, LOD observed in this work for p-coumaric acid was lower. Such trend was also verified when CoulArray was employed for polyphenols detection [ 47 , 51 ] with LODs estimated in the present study for vanillic and caffeic acids being similar or lower than previously reported. Use of PAD for cleaning and reactivation of GCE surface probably promoted such increase of sensitivity in relation to other methods, mainly when phenolic acids with high predisposition to adsorption and polymerization, as vanillic and p-coumaric acids, on the electrode surface.…”
Section: Resultssupporting
confidence: 91%
“…In comparison with other reports that employed HPLC-ECD [ 35 , 47 , 48 ] for phenolic acid detection, LOD observed in this work for p-coumaric acid was lower. Such trend was also verified when CoulArray was employed for polyphenols detection [ 47 , 51 ] with LODs estimated in the present study for vanillic and caffeic acids being similar or lower than previously reported. Use of PAD for cleaning and reactivation of GCE surface probably promoted such increase of sensitivity in relation to other methods, mainly when phenolic acids with high predisposition to adsorption and polymerization, as vanillic and p-coumaric acids, on the electrode surface.…”
Section: Resultssupporting
confidence: 91%
“…This is the first report about the quantification of the total content of monomers and dimers of proanthocyanidins in rhizomes of Japanese, Bohemian and giant knotweed. Other authors reported only the contents of separate monomers ((+)-catechin and (−)-epicatechin) [ 7 , 8 , 23 ] and B-type dimers (specified as “procyanidin dimer B”) [ 7 , 8 ] in the rhizomes of Japanese [ 7 , 8 , 23 ] and giant [ 7 , 8 ] knotweed. The total contents of monomers and dimers expressed per dry mass of the plant material (DM) for all STSs were the highest in Japanese knotweed rhizomes (5.80 kg/t DM) and the lowest in Bohemian knotweed rhizomes (2.61 kg/t DM), while it was 4.53 kg/t DM in gi ant knotweed rhizomes ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…When the obtained LODs using amperometric detection were compared with previously published data, again the obtained values in this work were better or very similar to those reported (Zima et al ., ; Gao et al ., ). In the coulometric detection mode, our LOD values also are lower than those reported in previous studies (Jandera et al ., ; Kahoun et al ., ; Benova and Hájek, ). The very good LODs obtained for the three detection modes used in this work should be noted, especially using the coulometric detection.…”
Section: Resultsmentioning
confidence: 99%
“…Methods based on HPLC also have been developed for the determination of these compounds. Reverse‐phase (RP) HPLC usually has been employed for the analysis of complex mixtures of phenolic compounds (Schwarz et al ., ; Viñas et al ., ; Larcher et al ., ; Villa et al ., ; Zima et al ., ; Ali et al ., ; Kahoun et al ., ; Muñoz‐Muñoz et al ., ; Benova and Hájek, ; Gao et al ., ; Turek and Stintzing, ; Haddad et al ., ). Although the UV detector is the more common mode (Villa et al ., ; Ali et al ., ; Muñoz‐Muñoz et al ., ; Haddad et al ., ) other detection techniques, such as fluorimetry (Viñas et al ., ) and UV spectrophotometry combined with MS (Turek and Stintzing, ), also have been used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation